Preparation of biodegradable films based on modified Colombian starches from Ipomoea batatas, Manihot esculenta, Dioscorea rotundata and Zea mays. (23rd February 2019) - Torrenegra, M.; Solano, R.; Herrera, A.; León, G.
ABSTRACT: The purpose of this study was to determine the effect of different chemical modifications such as hydrolysis, esterification with docecinyl succinic anhydride (DDSA) and octenyl succinic anhydride (OSA), and acetylation with acetic anhydride on the physicochemical, morphological properties of 3 native Colombian starches selected for research ( Ipomoea batatas, Manihot esculenta, Dioscorea rotundata and Zea mays ) and USP Zea mays, as well as the influence on the mechanical properties of the biodegradable films prepared by the casting method. The physicochemical, mechanical and morphological properties were determined by Fourier Transform Infrared Spectroscopy (FTIR), Traction test and Scanning Electron Microscopy (SEM), respectably. The results obtained showed that the starch films modified by using DDSA were more strong and rigid, while the films modified with OSA and AA were more flexible and ductile.